2019
DOI: 10.1002/1878-0261.12433
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy targeting the elevated interleukin‐6 level reduces invasive migration of BRAF inhibitor‐resistant melanoma cells

Abstract: The identification of novel antimetastatic therapeutic targets is necessary for improved treatment of patients with acquired BRAF inhibitor‐resistant (BRAFi‐R) melanoma, in whom metastasis is a major concern. Our present study focused on the identification of such targets to explore novel antimetastatic therapeutic options for BRAFi‐R melanoma patients. We confirmed the development of BRAFi resistance in our BRAFi‐treated melanoma cell lines by demonstrating reduced sensitivity to BRAF inhibitors, increased ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…BRAF inhibitor resistance involves a range of transcription factors ( Table 2 ) [ 14 , 16 , 22 , 28 , 45 , 46 , 48 , 52 , 58 , 66 , 81 , 89 , 97 , 117 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ]. A transcriptomic analysis of BRAF inhibitor-resistant melanoma cells showed that some transcription factors were upregulated whereas others were downregulated [ 141 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BRAF inhibitor resistance involves a range of transcription factors ( Table 2 ) [ 14 , 16 , 22 , 28 , 45 , 46 , 48 , 52 , 58 , 66 , 81 , 89 , 97 , 117 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ]. A transcriptomic analysis of BRAF inhibitor-resistant melanoma cells showed that some transcription factors were upregulated whereas others were downregulated [ 141 ].…”
Section: Resultsmentioning
confidence: 99%
“…Epigenetic mechanisms may be targeted by inhibiting key transcription factors, such as WNT5 or STAT3 [ 134 , 135 , 222 , 240 ], or by the use of microRNA mimetics [ 59 ] or HDAC inhibitors [ 111 , 163 , 241 , 242 , 243 , 244 , 245 ]. HDAC inhibitors have also been investigated in combination with a CDK inhibitor with promising in vitro and in vivo activity [ 233 , 244 , 246 ].…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, patients receiving BRAF inhibitors (BRAFi) relapses after several months of monotherapy because of the acquired resistance (Nazarian et al, 2010). WNT5A was shown to play a crucial role in the process leading to the Vemurafenib resistance (Anastas et al, 2014;Mohapatra et al, 2018;O'Connell et al, 2013;Prasad et al, 2015;Webster et al, 2015). Therefore, we were interested to check whether RNF43 inhibits via its effects on WNT5A signaling cellular plasticity in response to Vemurafenib (PLX4032), a clinically used BRAF V600E inhibitor.…”
Section: Rnf43 Prevents Acquisition Of Resistance To Braf V600e Targeted Therapymentioning
confidence: 99%
“…4 IL-6 signals directly to tumor cells through at least three major signaling pathways, including janus-activated kinase 1/2 (JAK1/2)/signal transactivator of transcription 3 (STAT3), rat sarcoma (RAS)/mitogen-activated protein kinase (MAPK), and phosphoinositide-3 kinase (PI3K)/AKR Thymoma (AKT), contributing to tumor promotion by expansion and survival of malignant cells, neo-angiogenesis, and inflammation. [5][6][7][8][9][10][11] IL-6 can also be secreted from infiltrating myeloid cells such as tumor-associated macrophages, dendritic cells (DC) and myeloid-derived suppressor cells (MDSC), 8 12 and tumor-associated stroma such as cancer-associated fibroblasts, endothelial, or senescent cells, contributing to a dynamic tumor-fibroblast cross-talk in the tumor microenvironment. 13 High levels of IL-6 exist in many pathologic conditions including cancer and rheumatologic diseases.…”
mentioning
confidence: 99%